Cyrtidiorchis gerardii - Gutiérrez Morales, Nicolás (2017)
Cyrtidiorchis Rauschert is a small genus of some fve species distributed from Colombia and Venezuela to Peru, phylogenetically related to Sauvetrea Szlach. and Mormolyca Fenzl (Maxillarinae). Tey are characterized by monopodial-growing stem arising from a sympo-dial, pseudobulb-bearing, basal rhizome. Tree species of Cyrtidiorchis are reported from Colombia, C. gerardi is endemic to the country. It is most similar to C. rhomboglossa and we have our reservations about their distinctness. Cyrtidiorchis gerardi can be recognized by spreading sepals and petals, and the relatively flattened lip with an incurved apex.